2017
DOI: 10.1016/j.jcrysgro.2016.10.028
|View full text |Cite
|
Sign up to set email alerts
|

Study on nucleation kinetics of lysozyme crystallization

Abstract: The nucleation kinetics of hen egg-white lysozyme crystallization was investigated using a hot stage cooling crystallizer and a microscope to monitor the solution crystallization process in real time. Images of crystals were continuously recorded under varied precipitant and protein concentrations. The nucleation rate was found to be higher at higher precipitant concentration, and increase monotonically with protein concentration if the precipitant concentration was held 2 constant. Attempt was made to interpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
4
11
0
Order By: Relevance
“…For the same concentration of lysozyme, the induction time was significantly decreased when there was an increase in NaCl concentration up to 1.1 M. In the high supersaturation region, (NaCl concentration above 1.1 M or lysozyme concentration above 100 mg/mL) there were reduced effects of the concentrations of lysozyme or NaCl, and very short induction times were obtained under these conditions. Lin et al [25] reported a similar dependence of the induction time on the reactants concentrations, in which a monotonic reduction in induction time was observed with an increase of the NaCl concentration or lysozyme concentrations, in agreement with the results shown in Figure 2. In the experiments with a single air bubble in the hanging drop, Figure 3 (a) shows that some crystals were attached to the bubble surface.…”
Section: Methodssupporting
confidence: 87%
“…For the same concentration of lysozyme, the induction time was significantly decreased when there was an increase in NaCl concentration up to 1.1 M. In the high supersaturation region, (NaCl concentration above 1.1 M or lysozyme concentration above 100 mg/mL) there were reduced effects of the concentrations of lysozyme or NaCl, and very short induction times were obtained under these conditions. Lin et al [25] reported a similar dependence of the induction time on the reactants concentrations, in which a monotonic reduction in induction time was observed with an increase of the NaCl concentration or lysozyme concentrations, in agreement with the results shown in Figure 2. In the experiments with a single air bubble in the hanging drop, Figure 3 (a) shows that some crystals were attached to the bubble surface.…”
Section: Methodssupporting
confidence: 87%
“…Thus, the known effectiveness of sucrose as a cryoprotectant could be confirmed with these observations [45,46]. The dominating cluster formation of Cl V and Cl VI and spread towards lower excipient concentrations mimics the above stated line of argumentation, namely an increase in the nucleation rate due to freeze concentration [17,62,66,68]. For glycerol containing systems, FT stress application resulted in a smaller occurrence of Cl I and a decrease in solubility, but less significant than for NaCl formulations, see Figs.…”
Section: Ft Cycle-ft C1 and Ft C3supporting
confidence: 56%
“…For Cl III the growth time (t G ) is smaller, however, this cluster was mainly seen for higher lysozyme concentrations, thus a higher supersaturation [61] and as a consequence enhanced creation of critical nuclei [62,63]. Higher supersaturation is assumed to correlate to shorter growth time, which results of crystal growth to bigger sizes.…”
Section: Initial State-ft C0mentioning
confidence: 99%
“…It appears that high cooling rate causes high supersaturation; as a result, the nucleation was induced during the early stage of the crystallization [33,42]. Moreover, because the rate of nucleation is high at high supersaturation (or the rate of nucleation is low at low supersaturation) while the stirring rate is fixed [41,42], the particle concentration changed more quickly, thus the crystals were more readily observed.…”
Section: Effect Of Cooling Rate On 5-ml Agitated Batch Crystallizatiomentioning
confidence: 99%
“…The solubility data of HEWL has been previously obtained and fitted by Lin et al [42]. The empirical equation of lysozyme solubility (10% (w/w) NaCl) can be expressed as follows:…”
Section: Effect Of Cooling Rate On 5-ml Agitated Batch Crystallizatiomentioning
confidence: 99%